Leadership and governance in a crisis: some reflections on COVID-19. Issue 4 (13th November 2020) - Mather, Paul
Abstract : Purpose: The COVID-19 crisis presents significant leadership and governance challenges and opportunities for organisations. This is a reflective commentary on how leaders and boards are responding to the crisis. Design/methodology/approach: Drawing on personal experiences as an employee, non-executive director and observing leaders. Findings: That leaders emphasise values and purpose and communicate with clarity, meaning and empathy is paramount. It is organisations which continue to be agile and to adapt and change proactively with "out of the box" thinking who will thrive in the next normal. Originality/value: The lessons learned from this unique crisis for business continuity and success in the next normal.